2021
DOI: 10.1200/jco.2021.39.15_suppl.5500
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety results from neopembrov study, a randomized phase II trial of neoadjuvant chemotherapy (CT) with or without pembrolizumab (P) followed by interval debulking surgery and standard systemic therapy ± P for advanced high-grade serous carcinoma (HGSC): A GINECO study.

Abstract: 5500 Background: To investigate whether adding Pembrolizumab (P) to neoadjuvant carboplatin-paclitaxel chemotherapy (CP) may increase the optimal debulking rate, assessed by Complete Resection Rate (CRR) after Interval Debulking Surgery (IDS) in patients (pts) with initially unresectable International Federation of Gynecology and Obstetrics (FIGO) stage IIIC/IV ovarian, tubal or peritoneal HGSC. Methods: Multicenter, open-label, non-comparative randomized phase II trial. Pts were randomized (2:1) to receive 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Patients receiving nivolumab showed increased proliferation of tumor infiltrating and peripheral T cells (30). The addition of anti-PD-L1 blockade to the perioperative chemotherapy treatment has since been evaluated in several clinical trials and found to be safe and effective (31,32). Such a protocol might well reduce the recurrence rate in patients that undergo resection of colorectal liver metastasis by targeting innate immune cells expressing PD-L1 that are found within the operative site after tumor resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients receiving nivolumab showed increased proliferation of tumor infiltrating and peripheral T cells (30). The addition of anti-PD-L1 blockade to the perioperative chemotherapy treatment has since been evaluated in several clinical trials and found to be safe and effective (31,32). Such a protocol might well reduce the recurrence rate in patients that undergo resection of colorectal liver metastasis by targeting innate immune cells expressing PD-L1 that are found within the operative site after tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving nivolumab showed increased proliferation of tumor infiltrating and peripheral T cells ( 30 ). The addition of anti-PD-L1 blockade to the perioperative chemotherapy treatment has since been evaluated in several clinical trials and found to be safe and effective ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study did not show any difference with the addition of pembrolizumab. 86 In conclusion, while endometrial and CCs are ready for prime-time immunotherapy clinical trials in the neoadjuvant setting, OC still has a long way to go where the value of current neoadjuvant immunotherapy-based regimens appears to be limited.…”
Section: Gynecologic Malignanciesmentioning
confidence: 98%
“…In the neoadjuvant setting, pembrolizumab has been investigated in combination with carboplatin and paclitaxel for four cycles, followed by interval debulking surgery and standard adjuvant treatment (+/− bevacizumab) with or without pembrolizumab up to 2 years in a phase 2 randomized trial, and the results have been presented at the 2021 American Society of Medical Oncology (ASCO) conference [ 43 ]. The addition of the immune checkpoint inhibitor resulted in a small increase in ORR and complete cytoreduction rate without difference in median PFS.…”
Section: Immune Checkpoints In Eocmentioning
confidence: 99%